Bias Against Indigenous Women and Sex Workers as Victims of Violent Crime - Knoop, Janelle (Race and social problems, 2025)
Indigenous women and sex workers experience high rates of violence in Canada, and research and media discourse suggest that they are often blamed for their victimization. This jury simulation study examined how victim race (Indigenous, White) and work in the sex trade (sex worker, non-sex worker) affected mock juror verdicts in a first-degree murder trial; to avoid confounding as a function of interracial/intraracial crimes, we also manipulated defendant race (Indigenous, White). Participants were Canadian jury-eligible community members (N = 427) recruited online via Qualtrics panels. After reading a trial transcript in which the victim’s race and occupation were varied, mock jurors provided a verdict and responded to questions regarding the victim and other trial parties. Results revealed that mock jurors assigned more negative stereotypes to the victim when she was Indigenous and when she was a sex worker, and that sex worker victims were perceived as more blameworthy. Although direct effects of our manipulated variables on verdict were weak, a moderated mediation analysis revealed that victim blame is significantly predicted by victim occupation, feelings towards sex workers, and negative stereotypes. Because we also observed that victim blame predicts verdict decisions, this has implications for the potential treatment of victims of violent crime who work in the sex trade.